Assessment of the relationship between Cultural Identity and Social Integration among Students in Higher Education Institutions: A Focus on IBB University Lapai, Niger State, Nigeria - Dauda, Juliana Hussaina (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
The paper examines the relationship between cultural identity and social integration among students in higher education institutions with a focus on Ibrahim Badamasi Babangida University Lapai (IBBUL), Niger State-Nigeria. The cultural diverse multiplicity and interactions were found to be a common feature in IBBUL just like any other tertiary education institution in Nigeria. Some of the objectives of the study are to examine the relationship between cultural identity and social integration among students and identify factors that facilitate or hinder social integration among students of IBBUL through triangulation. Social identity theory was adopted. A descriptive survey design was adopted, with a sample size of 393 determined through Taro Yamane’s formula. Out of these, 350 questionnaires were retrieved, giving a response rate of 89.3%. Data were analyzed using descriptive statistics, chi-square tests, and thematic analysis for open-ended responses (interviews, FGDs). Key findings include: strong pride in cultural heritage (85%), but a majority also admitted that cultural identity influences their social relationships (75.7%). Most students (78.6%) reported having friends outside their cultural group and 87.2% believed that diversity enriches campus life. However, 54.3% still reported feeling isolated at times. Barriers to integration included language differences (61.5%) and stereotypes (64.3%). Enabling factors included social events (62.9%), faculty support (61.4%), and mutual respect (74.3%). These findings suggest that while cultural identity remains central to students’ experiences, positive attitudes toward diversity and mutual respect provide strong foundations for social cohesion if well harnessed by institutional policies Keywords: Cultural Identity, Social Integration, Diversity, Ethnic Group, Stereotype, Cultural Exchange